HUMAN RESOURCE MANAGEMENTSTRATEGIES FOR MANAGING THEAGINGWORKFORCE IN INDIAN HOSPITALITYFIRMS - CHAND, MOHINDER (ASEAN Journal on Hospitality and Tourism, 2009)
This paper examines the critical issues relating to the management of aging workforce in the Indian hospitality firms. It is based on an e-mail survey of 250 hospitality firms, supplemented by 28 indepth interviews with HR manager- owners located in the northern India. The results indicated that a number of different HRM strategies are important for the efficient use of aging workforce in Indian hospitality firms related to the work-life balance and flexible work practices ,workforce planning, Career planning & development, retirement & pensions, knowledge management, training & development and so forth. These findings suggest that HRM strategies might be crucial to the management of aging workforce in the Indian hospitality firms.